Students' meaning-making strategies in their reading of canonical texts and young adult literature - Perumal, Rajandaran (2012)
The objectives of this study were to record and discuss students’ meaning-making strategies in reading canonical texts and young adult literary texts (YAL). The researcher wanted to study students’ meaning-making strategies to study if these strategies can provide evidence to what would be pedagogically appropriate literary texts in the classroom. The data was collected using three methods. First, the participants read two novels and kept an online journal. The participants wrote journal responses for both the canonical text and YAL. Second, the participants responded to prompts in an online forum. Third, the participants were interviewed. The study indicated that the most frequent meaning-making strategies used by the participants were synthesizing, determining importance, making connections,predictions, visualizing, questioning, monitoring, use of intertextuality and using the Internet and on-line applications. One major finding was that the participants used more meaning-making strategies when the literary text that they were reading presented more reading challenges. One difference in the use of meaning-making strategies was that on-line applications were used only in reading the canonical texts: Wuthering Heights and Great Expectations. The implications discussed include the use of YAL as a classroom text. It discussed using young adult literary text as a ‘bridge’ to read and understand canonical texts. Participants’ effortless use of technology in searching for ways to help in their meaning-making strategy was also discussed as an implication of bringing and using technology, for example, movies based on novels, in the reading of literature. Text selection is important in drawing students’ interest in reading literary texts. Providing opportunities for students to make connections with literature in the classroom and outside the classroom should be the objective of all teachers who use any category of literary texts in the teaching and learning of literature.